The Effectiveness of Google Classroom Media in Improving Student Learning Outcomes at Junior High School: Efektivitas Media Google Classroom Dalam Meningkatkan Hasil Belajar Siswa di SMP - Santi Irawati; Eni Fariyatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
The establishment of the COVID-19 outbreak as a global pandemic has an impact on all lines of life. In the field of education led to the implementation of a distance learning system. One of the media that supports distance learning is Google Classroom. Google Classroom is an application that can be used as a classroom in a virtual world with various existing facilities. This study aims to determine the effectiveness of the Google Classroom media in improving student learning outcomes at Hang Tuah 5 Middle School Sidoarjo. This study uses a quantitative approach to the type of experiment with a pretest-posttest control group design. The population is class VII students totaling 178 students. The samples were several students from class VII-B (control class) and VII-C (experimental class) with purposive sampling method. The results of the data analysis test using the Paired sample t-test obtained the value of Sig (2-tailed) 0.000. If the value of Sig (2-tailed) <0.05, then HO is rejected and Ha is accepted, meaning that PAI learning with Google Classroom media is effective in improving student learning outcomes at Hang Tuah 5 Middle School Sidoarjo.